2019
DOI: 10.1186/s12960-019-0433-x
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying and its impact on the quality of healthcare and patient safety

Abstract: BackgroundWorkplace bullying (WPB) is a physical or emotional harm that may negatively affect healthcare services. The aim of this study was to determine to what extent healthcare practitioners in Saudi Arabia worry about WPB and whether it affects the quality of care and patient safety from their perception.MethodsA cross-sectional study was conducted in 2018. An online survey was distributed among all practitioners at a multi-regional healthcare facility. A previously validated tool was sourced from an integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 30 publications
2
73
0
3
Order By: Relevance
“…For nurses, in particular, who are with patients 24 hours a day 7 d/wk, increased infection rates of central lines, 33 medical errors, 34 and suboptimal standards of practice resulted. 36 Porath and Pearson found that 66% of workers admitted that their own performance in the workplace had declined significantly, 37 38% intentionally decreased their quality of work, and 48% intentionally decreased their work effort; others just lost interest. 36,38,39 Workplace bullying compromised nurse safety, well-being, and patient-centred safe work practices.…”
Section: The Liabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For nurses, in particular, who are with patients 24 hours a day 7 d/wk, increased infection rates of central lines, 33 medical errors, 34 and suboptimal standards of practice resulted. 36 Porath and Pearson found that 66% of workers admitted that their own performance in the workplace had declined significantly, 37 38% intentionally decreased their quality of work, and 48% intentionally decreased their work effort; others just lost interest. 36,38,39 Workplace bullying compromised nurse safety, well-being, and patient-centred safe work practices.…”
Section: The Liabilitymentioning
confidence: 99%
“…36 Porath and Pearson found that 66% of workers admitted that their own performance in the workplace had declined significantly, 37 38% intentionally decreased their quality of work, and 48% intentionally decreased their work effort; others just lost interest. 36,38,39 Workplace bullying compromised nurse safety, well-being, and patient-centred safe work practices. 40 Physicians, also compromised patient safety due to their low morale, 41 threw bloody instruments at nurses in the Operating Room (OR), as well as shamed, humiliated, and spread malicious rumours about colleague nurses.…”
Section: The Liabilitymentioning
confidence: 99%
“…WPB negatively affects patients' safety and quality of care [13]. Studies found that the intimidating and disruptive behaviors associated with WPB fuel medical errors and lead to adverse outcomes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…WPB negatively affects patients' safety and quality of care [13]. Studies found that the intimidating and disruptive behaviors associated with WPB fuel medical errors and lead to adverse outcomes [13,14]. In addition to being a dramatic threat to patient safety [15], WPB declines staff morale and increases absenteeism, leading to a high turnover rate of qualified staff [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation